High sensitivity Double Split Ring Resonator – Defected Ground Structure (DSRR-DGS) based microwave sensors for material characterization - Misran, Mohamad Harris; Meor Said, Maizatul Alice; Othman, Mohd Azlishah; Salleh, Azahari; Shadia, Suhaimi; Idris, Mohd Zahid (2024)
Microwave sensors have emerged as indispensable tools in material characterization, offering high sensitivity, non-invasive measurement capabilities, and functionality in challenging environments. However, traditional designs often suffer from low sensitivity and poor accuracy due to limited coupling efficiency and low-quality factor (Q-factor), which constrain their applicability in precision-demanding fields. To overcome these challenges, this study proposes a novel microwave sensor based on a defected ground structure (DGS) design integrating symmetrical and complementary split-ring resonator (SRR) configurations. These innovations significantly enhance field confinement and resonance quality, leading to improved sensitivity and accuracy. The sensor was designed, analyzed and fabricated for experimental validation. Key performance metrics, including a high Q-factor of 398, a sensitivity of 168 MHz/εr, and an accuracy of 99.68%, were achieved. The combination of high accuracy, superior Q-factor, and exceptional sensitivity positions this sensor as a state-of-the-art solution for applications in biomedical diagnostics, industrial quality control, and environmental monitoring.